Specialized herbivore on inflorescence stalks of Trichocentrum undulatum (Orchidaceae) by Melanagromyza sp. (Diptera: Agromyzidae) in Cuba - Borrero, Haydee (Universidad de Costa Rica, 2018)
Inflorescence stalk herbivory on the Mule Ear orchid (Trichocentrum undulatum) has been observed in Cuba, which resembles the specialized herbivory interaction seen in southern Florida between a specialized dipteran, Melanagromyza miamensis (Agromyzidae) and the Mule Ear orchid. We are able to identify the inflorescence herbivore to be the genus Melanagromyza. It is possibly the same species that can be found in southern Florida. The mule-ear orchid is endemic to the Caribbean region, i.e. Cuba, Jamaica and southern Florida. To our knowledge, this is the first report of an apparently specialized inflorescence stalk herbivory by Agromyzid flies on the Mule Ear orchid in Cuba. The herbivory can partially or completely destroy the flowering potential of the impacted plants.